Comparison of early outcomes between unicompartmental and total knee arthroplasty in patients with anteromedial compartment knee osteoarthritis and class II obesity: a retrospective case analysis - Li, Qingwei; Zhai, Shenhao; Mu, Zongyou; Zhang, Xubin (Frontiers in Surgery, 2025)
BackgroundThis study compared early clinical outcomes of unicompartmental knee arthroplasty (UKA) and total knee arthroplasty (TKA) in patients with anteromedial osteoarthritis (AMOA) and class II obesity during postoperative hospitalization and at 1, 6, and 8 months postoperatively.MethodsA retrospective analysis was conducted on 85 patients with class II obesity who underwent UKA (n = 45) or TKA (n = 40) between January 2022 and January 2024. Perioperative parameters, including operative time, incision length, hemoglobin and albumin levels on postoperative day 2, and hospital stay, were compared. Functional outcomes were assessed using the visual analog scale (VAS), Hospital for Special Surgery (HSS) knee score, and range of motion (ROM) before surgery and at 1, 6, and 8 months postoperatively. Complication rates were also recorded.ResultsAll patients completed surgery successfully. The UKA group had significantly shorter operative times, smaller incisions, higher postoperative hemoglobin and albumin levels, and shorter hospital stays (P < 0.01). At 1 and 6 months, UKA patients showed better VAS, HSS scores, and ROM (P < 0.05). By 8 months, no significant differences remained. Complication rates were lower in the UKA group (2.22%) than in the TKA group (17.5%) (P < 0.05).ConclusionBoth UKA and TKA improve pain and function in AMOA patients with class II obesity. However, UKA offers advantages in perioperative recovery, early functional outcomes, and complication rates, supporting its use in appropriately selected patients.